Preparation, and physicochemical and biological evaluation of chitosan‐Arthrospira platensis polysaccharide active films for food packaging. Issue 3 (18th February 2021) - Luo, Aiguo; Hu, Bianfang; Feng, Jia; Lv, Junping; Xie, Shulian
Abstract: Active films from chitosan incorporated with Arthrospira platensis polysaccharide (APP) of various ratios (0.0%, 0.5%, and 1.0%, w/v) were developed by solution casting. The effect of APP on the structural, physicochemical, mechanical, antimicrobial, and antioxidant properties of the chitosan‐APP films (CA‐film) was investigated. Fourier transform infrared spectra (FTIR) confirmed successful incorporation of chitosan and APP. The compact structure of the films was observed clearly in scanning electron microscopy (SEM) and atomic force microscopy (AFM) images. X‐ray diffraction (XRD) patterns suggest the semi‐crystalline structure was increased upon addition of APP. The composite films showed an improved water resistance and vapor barrier properties, and reduced by at least 27.4% and 32.1% in swelling degree ( Sd ) and water vapor permeability ( WVP ) compared with chitosan film (C‐film), respectively. However, the transparency decreased slightly, which may be due to the shrinkage of the spacing of the polymer interchain. The composite films also displayed enhanced the mechanical properties. The antimicrobial activity of the CA‐film showed an increase of at least of 0.41‐fold in inhibition zone diameter for E. coli . At a concentration of 1.2 mg/mL, the antioxidant activity of CA‐film was enhanced by more than threefold compared with C‐film. Therefore, CA‐films have good potential as sources of active packaging material for the food industry.